Memoirs of an addicted brain : a neuroscientist examines his former life on drugs - Lewis, Marc (PublicAffairs, 2012)
A neuroscientist tells the story of his youth spent as a drug addict, while using the specific example of his own story to help explain drug use and addiction in general from a scientific standpoint.